Perinatal Risk Factors of Thrombocytopenia among Newborns Admitted to Neonatal Care Unit - جوني, عدي (Latakia University Journal -Medical Sciences Series, 2020)
Thrombocytopenia (platelet count <150,000 mm3) is one of the most common blood disorders in neonatal period. Sepsis, perinatal hypoxia, respiratory disorders, various congenital malformations, and intrauterine growth retardation are important risk factors for incidence of neonatal thrombocytopenia. Determining the risk factors responsible for thrombocytopenia is important to avoid complications that may be life-threatening. This study aimed to shed light on the neonatal risk factors responsible for neonatal thrombocytopenia, and to study the severity of thrombocytopenia according to the risk factor. A prospective observational study, conducted during the period from March 2018 until September 2019. All neonates who were subjected to intensive care or standard care units in the Neonatal Care Unit at Tishreen University Hospital were studied and scored a blood platelet count less than 150,000 / mm3 at least once.Perinatal risk factors were reported associated with all cases of thrombocytopenia. The study sample was divided into three groups, according to the severity of the thrombocytopenia. The number of admissions into the neonatal care unit during the study period was 781 newborns, (643 full-term, 138 preterm infants). Thrombocytopenia was recorded in 104 neonates (13.31%). 38.46% of it was severe. Sepsis was the most important risk factor (62.5%), as it was associated with severe thrombocytopenia, followed by perinatal asphyxia and congenital anomalies (14.42% and 15.38%, respectively), with moderate severity of thrombocytopenia. From the above, we concluded that thrombocytopenia may be considered as a diagnostic indicator in sick newborns, especially in sepsis.